PWE-375 A significant proportion of patients still require colonoscopy after ct colonography within the nhs bowel cancer screening programme. (22nd June 2015) - Sehgal, V; Harvey, E; Stein, J; Bloom, S; Vega, R; McCartney, S; Obichere, A; Besherdas, K
Abstract : Introduction: Patients within the Bowel Cancer Screening Programme (BCSP) who are unsuitable for or decline colonoscopy are instead usually offered CT colonography (CTC). Whereas patients with a normal CTC are either discharged or returned back to biennial screening, colonoscopy is usually indicated if CTC demonstrates a suspected colorectal cancer (CRC) or large polyp/s (>10mm). Patients who have intermediate-sized polyps (6–9mm) or multiple diminutive polyps (<5mm) either proceed to colonoscopy (flexible sigmoidoscopy for left-sided polyps) or interval CTC. We investigated the number of patients who required colonoscopy after CTC within the BSCP. We hypothesised that a significant proportion of patients still require colonoscopy, thus questioning the utility of CTC in patients in the BCSP. Method: Patients who had a CTC within the BCSP at UCLH between September 2007–14 were identified retrospectively. All CTC examinations were performed using faecal tagging with laxatives wherever possible with or without intravenous contrast. Results: of CTC were classified as normal, low-risk (1–2 polyps both <10mm), intermediate-risk (3–4 polyps <10mm or at least one ≥10mm), high-risk (≥5 small polyps or ≥3 intermediate-sized polyps with at least one ≥10mm) and suspected CRC. Results: In total, 319 CTCs were performed in 292 patients. 39 patients (13%) had CTC after incomplete colonoscopy and were excluded. 253 patients (136 male, median age 70 years) underwent CTC as their primary investigation and their outcomes analysed. 98 patients (39%) proceeded to having a colonoscopy after their CTC. There was no significant difference in the reported study quality between those patients requiring a colonoscopy (good 44%, poor 10%) and not (good 52% poor 7%). 57 patients (92%) who had either intermediate/high-risk polyps or suspected CRC on CTC underwent colonoscopy. Of these 57 patients, 15 (26%) had either low-risk polyps (n = 9) or no abnormality at colonoscopy (n = 6). 37 patients (20%) whose CTC was either normal (n = 10) or revealed low-risk polyps (n = 27) were also referred for colonoscopy. No patient had their CTC diagnosis upstaged after colonoscopy. The median time from CTC to colonoscopy was 35 days (5–1852 days). 72 patients (74%) had their colonoscopy within 3 months of their index CTC. Conclusion: A significant proportion of patients who undergo CTC within the BCSP will still require a colonoscopy. Although the sensitivity of polyp detection between CTC and colonoscopy is comparable, CTC confers a not insignificant radiation burden. It is essential that all patients be counselled with this information upon entrance into the BCSP and in doing so, may reduce the number of CTCs as the primary investigation within the BCSP. Disclosure of interest: None Declared.